2018
DOI: 10.3389/fpsyt.2018.00471
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects of Early Adolescent Stress on Depressive-Like Behaviors and Expression of Cytokines and JMJD3 in the Prefrontal Cortex and Hippocampus of Rats

Abstract: Aims: Expression of inflammatory cytokines in the brain has been reported to be involved in the pathogenesis of and susceptibility to depression. Jumonji domain-containing 3 (Jmjd3), which is a histone H3 lysine 27 (H3K27) demethylase and can regulate microglial activation, has been regarded as a crucial element in the expression of inflammatory cytokines. Furthermore, recent studies highlighted the fact that lipopolysaccharides induce depressive-like behaviors and higher Jmjd3 expression and lower H3K27me3 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
2
20
0
1
Order By: Relevance
“…The present study found that adolescent traumatic stress induced anxiety, exploratory behavior suppression, reduction of social exploratory behavior and impairment of spatial memory in rats. Such findings indicate that IFS induced post-traumatic stress-like behavioral disorders in young rats, and the symptoms could persist into adulthood in rats ( Wang R. et al, 2018 ). However, most of the above behaviors were improved by treatment with Unc0642, a small molecule inhibitor of EHMT2, which could reduce the protein expression level of H3K9me2.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study found that adolescent traumatic stress induced anxiety, exploratory behavior suppression, reduction of social exploratory behavior and impairment of spatial memory in rats. Such findings indicate that IFS induced post-traumatic stress-like behavioral disorders in young rats, and the symptoms could persist into adulthood in rats ( Wang R. et al, 2018 ). However, most of the above behaviors were improved by treatment with Unc0642, a small molecule inhibitor of EHMT2, which could reduce the protein expression level of H3K9me2.…”
Section: Discussionmentioning
confidence: 93%
“…Exposure to a harsh environment has a negative impact on brain structure that may lead to impairment of cognitive and emotional function in humans ( Wang R. et al, 2018 ; Xu et al, 2019 ). Also, experiencing stress in early childhood may easily affect neuronal structure and function, thereby leading to substance abuse, anxiety, depression and even learning function and social communication impairments ( Salzmann-Erikson and Hicdurmaz, 2017 ; Cowan et al, 2018 ; Postel et al, 2019 ; Ohta et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, histone modification includes acetylation, methylation, ubiquitylation, phosphorylation, SUMOylating, ribosylation, and citrullination. Among them, acetylation is the most highly studied in mental disorders ( Levine et al, 2012 ; Seo et al, 2016 ; Wang et al, 2018 ; Karen and Rajan, 2019 ). Histone modification can loosen or tighten the chromosome to alter transcription.…”
Section: Overview Of Epigeneticsmentioning
confidence: 99%
“…Moreover, histone modifications also modulated the pro-inflammatory characteristics in rats exposed to the ELS. It was assumed that chronic unpredictable mild stress during the adolescence period combined with maternal separation induced depressive-like behaviors, burst cytokines, and increased Jmjd3 (a histone H3 lysine 27 (H3K27) demethylase) and decreased H3K27me3 expression in the prefrontal cortex and hippocampus of both adolescent and adult rats ( Wang et al, 2018 , 2020 ). Therefore, compared with the studies of the site-specific profile of DNAm, DNAm, and histone regulators seemed to have a more profound effect.…”
Section: Epigenetic Studies Focused On Animalsmentioning
confidence: 99%
“…The exact profile of cytokine alterations depends on timing of stress, region assessed and timing of assessment. Less research has been directed at post-weaning and adolescent phases, but peripheral and central cytokine expression is also affected by chronic unpredictable stress and isolation rearing throughout adolescence, especially TNFα, IL-1β and IL-6 (Ko and Liu, 2015, 2016; Moller et al, 2013; Shortall et al, 2018; Wang et al, 2018b). Restraint and social defeat during adolescence enhance the expression of IL-1β and TNFα in the hippocampus after immune challenge, effects that are not mirrored in the periphery (Bekhbat et al, 2019; Pyter et al, 2013).…”
Section: Early Life Experiences and Neuroimmune Functionmentioning
confidence: 99%